A Proposed Technique for Solving Linear Fractional Programming - Sarmd A. Salih (Journal of Madenat Alelem University College, 2014)
Linear fractional programming (LFP) problems are useful tools in production planning, financial and corporate planning, health care and hospital planning and as such have attracted considerable research interest. The paper presents a new approach for solving a fractional linear programming problem in which the objective function is a linear fractional function, while the constraint functions are in the form of linear inequalities. We illustrate a number of numerical examples to demonstrate a proposed technique. We then compared proposed technique with Cooper’s method in the literature for solving (LFP) problems.